2023
DOI: 10.1021/acs.langmuir.3c00396
|View full text |Cite
|
Sign up to set email alerts
|

Active Droplet Transport Induced by Moving Meniscus on a Slippery Magnetic Responsive Micropillar Array

Abstract: Intelligent droplet manipulation plays a crucial role in both scientific research and industrial technology. Inspired by nature, meniscus driving is an ingenious way to spontaneously transport droplets. However, the shortages of short-range transport and droplet coalescence limit its application. Here, an active droplet manipulation strategy based on the slippery magnetic responsive micropillar array (SMRMA) is reported. With the aid of a magnetic field, the micropillar array bends and induces the infusing oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Motile cilia widely exist in many organs and play a crucial role in the transport of substances like sputum and ova 61–63 . Similar to motile cilia, magnetically responsive microcolumn or microcilia can produce controllable bending, clustering, or stiffness change under the action of a magnetic field, and can be used to transport droplets 58,59,64–73 . In order to distinguish clearly, we refer to the elongated structures with identical morphology (shape and size) and regular arrangement prepared by molding method as microcolumn structures 58,64–66,73 .…”
Section: Magnetically Responsive Manipulation Of Dropletsmentioning
confidence: 99%
See 2 more Smart Citations
“…Motile cilia widely exist in many organs and play a crucial role in the transport of substances like sputum and ova 61–63 . Similar to motile cilia, magnetically responsive microcolumn or microcilia can produce controllable bending, clustering, or stiffness change under the action of a magnetic field, and can be used to transport droplets 58,59,64–73 . In order to distinguish clearly, we refer to the elongated structures with identical morphology (shape and size) and regular arrangement prepared by molding method as microcolumn structures 58,64–66,73 .…”
Section: Magnetically Responsive Manipulation Of Dropletsmentioning
confidence: 99%
“…Similar to motile cilia, magnetically responsive microcolumn or microcilia can produce controllable bending, clustering, or stiffness change under the action of a magnetic field, and can be used to transport droplets 58,59,64–73 . In order to distinguish clearly, we refer to the elongated structures with identical morphology (shape and size) and regular arrangement prepared by molding method as microcolumn structures 58,64–66,73 . The self‐assembled elongated structures with different sizes and random distributions created by Rosensweig instability are called microcilia structures 59,67–72 .…”
Section: Magnetically Responsive Manipulation Of Dropletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with those actuated by other actuation methods including electric field, light, , and thermal field, magnetically actuated droplet robots can be controlled by using noninvasive magnetic fields to accomplish complex operations and on-demand tasks without generating heat and pollution and the robot is not affected by the object light transmittance as well. Thus, human and environmentally friendly droplet robots play a significant role in microfluidics, object manipulation, ,, chemical reactions, ,, targeted drug delivery, , and pressure sensor . However, existing droplet robots always struggle to maintain fixed and complex shapes due to their fluidity, which makes them difficult to manipulate objects with large inertia.…”
Section: Introductionmentioning
confidence: 99%
“…28 Recently, responsive anisotropic slippery surfaces have been intensely studied and used to achieve intelligent control of droplet manipulation under external stimuli such as mechanical force, 31–34 light, 35–38 electricity, 39–44 and magnetism. 45–54 For instance, Khare et al reported a mechanically tunable slippery surface using lubricating silicone oil-coated PDMS-based anisotropic wrinkles for the slippery behavior. 34 Zhang et al produced a photothermally sensitive anisotropic slippery surface for controllable droplet manipulation using laser-structured graphene and polyvinylidene difluoride composites (L-G@PVDF).…”
Section: Introductionmentioning
confidence: 99%